Comparative analysis of the growth differences between hybrid Ningdu Yellow chickens and their parentals - Yanping Wu; Cong Huang; Yue Wei; Zhaofeng Kang; Weihong Zhang; Jinfang Xie; Ligen Xiong; Min Zhou; Guosheng Zhang; Rongjun Chen (Poultry Science)
ABSTRACT: Although the local high quality chicken breed in China has excellent flavor, its growth rate is inferior to that of foreign breeds. To improve the growth rate of local chicken breeds, it is crucial to study the mechanism of chicken muscle development. Herein, Ningdu Yellow chicken was used as the research object, and a new hybrid breed (W) was obtained by crossing the G, H and D lines, which combined the excellent physiological characteristics of its parents. Combined analysis of Ningdu Yellow chickens and their parents was carried out. Chickens from 105-day-old lines (W, G, H) were selected, and breast meat and serum were extracted for transcriptome sequencing and metabolome determination to study their growth differences. The live weight, carcass weight, half-eviscerated weight, eviscerated weight, and breast muscle weight of W were significantly higher than those of G and H. Differential expression analysis identified 1700 differentially expressed genes (DEG), and gene ontology and kyoto encyclopedia of genes and genomes (KEGG) analyses identified 33 and 1 pathways related to growth and development and steroid biosynthesis, respectively. Next, pairwise analysis identified 57 KEGG pathways, among which the MAPK signaling, steroid hormone biosynthesis, tight junction, and PPAR signaling pathways were involved in growth and development. Cluster analysis found that genes highly expressed in the W group were associated with regulation of the actin cytoskeleton, riboflavin metabolism, steroid biosynthesis, and glycerophospholipid metabolism. The top 2 clusters obtained by protein-protein interaction analysis were important for the growth and development of chickens. Finally, the metabolomic analysis found key differentially accumulated metabolites (DAM) that might be account for the growth differences. Further integrated analysis identified key DEGs and DAMs that might be responsible for the observed growth differences. This study identified genes governing growth traits in Ningdu Yellow chickens, laying a theoretical foundation for the development of chicken breeding, the utilization of hybrid supporting lines, and promotion of the Chinese chicken industry.